Concepções linguísticas e luta política: língua Tikuna, línguas indígenas e políticas línguísticas na Região do Alto Solimões - Flores (Tchobücü rü Goecü) Tikuna, Sansão Ricardo (2018)
This dissertation intends to show the importance of creating new ways of seeing Indigenous languages which, within a certain historical period, were shaped by different conceptions. One of these perceptions was of its irrelevance within the linguistic policies determined by the Portuguese language and, in an opposing situation, of its new gained value thanks to the historical mark presented by the Brazilian Constitution of 1988. In our presentation, we focused on the Tikuna (Ticuna) people who, during the past decade, in spite of the new policies created with the 1988 Constitution, have had their culture and their language greatly influenced by the outside world in the areas of education, health, and of other public policies which, in one way or the other, has produced a large amount of linguistic modifications within the Tikuna langage, especially in areas of greater vulnerability. This research intendsto report on themesrelated to how the Indigenous world survived during the past five centuries. Focused on the political and linguistic struggles, it has as its standing point the Tikuna (Ticuna) and for field study, the communities in Santo Antonio, in Benjamin Constant/ Amazonas. Its main purpose is to contribute to the creation of a new panorama of the history of Maternal languages of the Indigenous peoples, with a new renovating paradigmatic category.